ANALISIS KARAKTERISTIK GETARAN PADA KERETA API REL LISTRIK DAN KERETA API REL DIESEL - Achmad Suwandi; Daryono Restu Wahono; Denny Hermawanto (JURNAL STANDARDISASI, 2009)
Vibration monitoring was carried out in two type of trains, namely Railroad Electric Train (KRL) and RailroadDiesel Train (KRD). From measurement results, it was clearly seen that both trains indicate the similar vibrationcharacteristics, where three dominant frequencies, so called: f1, f2 and f3 always appeared in the region offrequency measurement: 1Hz – 80Hz. The maximum vibration level in KRL was found to be 0.17m/s2 at f3(40Hz)in longitudinal direction and 0.164m/s2 at f3(50Hz) in transversal direction. Meanwhile, the maximum vibrationlevel in KRD was found to be 0.37m/s2 at f3(80Hz) in longitudinal direction and 0.354m/s2 at f1(2Hz) in transversaldirection. Based on these results, it is proved that the vibrations in KRD were much higher than the vibrations inKRL. However it is important to be noted, that the vibration levels of both trains were still within allowable limitwhich is recommended by Standard ISO 2631/I (1985).